PemanfaatanSpreadsheet (Google Sheet) dalam Pengembangan Sistem Informasi Inventaris Peralatan pada Gereja XYZ di Kota Salatiga - Purwanto, Purwanto - (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2025)
Spreadsheet is a familiar application, and many people use it to record data in tabular form and process data, which makes it very easy to create the information needed faster. Nowadays, spreadsheets can be implemented using Google Sheets. The Community Service Program was carried out at XYZ Church in Salatiga City using the spreadsheet application. Activity Objective: Help churches to have an equipment inventory information system and mentor the use of information systems. Using Google Sheets (spreadsheet) applications so that they can help churches record and organize a number of inventories effectively and efficiently. Using the PRA (Participatory Rapid Appraisal) method and following stages such as initial surveys, problem identification, alternative solution design, system development, system training, and application use assistance for parties related to church inventory. Application development using Google Sheets by using the App Sheet module to create the user interface, while the database still uses sheets in the spread sheet. The training was given to representatives per category. The implementation of community service is likely successful because of the training participants who agree on average above 75%, those who are neutral on average below 25%, and those who are not neutral 0%. The results of the equipment inventory information system model from this community service can be used as an example for other churches in the city of Salatiga